An Extension of Fermatean b-Derived Fuzzy Soft Ternary Subgroup (Global Journal of Science Frontier Research, 2023)
Soft set fermatean uncertainty set n-dimensional extension subgroup k-cut extension homomorphism ternary group b-derived fermatean uncertainty ternary subgroup
Keywords: soft set; fermatean uncertainty set; n-dimensional; extension; subgroup; k-cut; extension homomorphism